(untitled) (International Journal of Irrigation and Water Management, 2023)
Field experiments were conducted during the winter season of 2003 -04 and 2004 -05 to determine the effect of mulch in relation to irrigation and planting method on soil temperature, weed control, baby corn growth, water use and yield. The study revealed that bed planting of baby corn caused 34.9% increase in yield over ridge planting method. Plastic mulch increased baby corn yield by 18.9% and 77.5% over rice straw and unmulched treatment respectively. Baby corn yield at irrigation level of 1.2 ETc proved significantly superior to 1.0 ETc and 0.8 ETc levels. The study further revealed that plastic mulch at irrigation level of 0.8 ETc resulted significant increase in yield by 28.6% over unmulched soil condition even when it was irrigated at 1.2 ETc and resulted 30.6% of water saving. It was interesting that in bed planting method, plastic mulch caused statistically same baby corn yield at all the levels of irrigation with maximum water use efficiency of 40.1 kg/ha-cm at irrigation level of 0.8 ETc, while in ridge planting method the baby corn yield was statically same only at irrigation level of 1.2 ETc and 1.0 ETc, while at 0.8 ETc it decreased significantly.